Outage probability analysis in DF power-splitting full-duplex relaying network with impact of Co-channel interference at the destination - Phu Tran Tin; Duy Hung Ha; Minh Tran (Universitas Ahmad Dahlan, 2020)
Nowadays, improving the WPCN efficiency problem is the leading research direction in the communication network. In this research, the outage probability (OP) analysis in DF power-splitting (PS) full-duplex (FD) relaying network with impact of co-channel interference at the destination is proposed and investigated. In the system model section, we present the DF PS FD Relaying Network with Impact of Co-channel interference at the destination. Then in the system performance section, we analyze and derive the closed-form expression of the OP and investigate the effect of the main system parameters on the system network performance. Then, we perform the Monte Carlo simulation to verify the analytical section. This research can provide a new recommendation for the communication network.